POTENSI EKSTRAK HEKSAN DAUN KAPUR (Harmsiopanax aculeatus, Harms) SEBAGAI OBAT ANTIMALARIA - Salenussa, Jusuf; Wijaya, Jefry; Labetubun, Colincie Natalia; Belseran, Stenly Erwin (Program Kreativitas Mahasiswa - Penelitian, 2014)
Kapur plant (Harmsiopanax aculeatus, Harms) is traditionally used by Mollucans to treat malaria disease. Squeezed of young leaves which is dropped on the eye of sufferer is the way of its treatment. This research is aimed to assay haem polymerization inhibition activity, cytotoxic activity toward vero cells and to analysis chemical secondary metabolit of compound content on hexane extract of the old kapur leaves. Dried powder of kapur leaves (1 kg) is extracted by maceration technique using hexane solvent obtained 24.34g (2.43%) of hexane extract. Those extract which assayed haem polymerization inhibition on activity by Bassilico et al. (1998) method and cytotoxic test toward vero cells using MTT assay. Probit analysis has showing us that hexane extract of ripe kapur leaves were inhibit haem polymerization actively with IC50 in the amount 59.473 µg/mL and were not toxic toward normal cells with IC50 in the amount 1270.746 µg/mL. Phytochemical analysis by spray and visible reagent shown of steroid compound. Keywords:  Harmsiopanax acuelatus Harms, haem polymerization inhibition activity, cytotoxic activity, vero cell, phytochemical